The effects of monosodium glutamate as an alternative fertilizer towards the growth of zea mays / Ahmad Faris Seman@Kamarulzaman and Mohamad Asyraf Mohamad - Seman@Kamarulzaman, Ahmad Faris; Mohamad, Mohamad Asyraf (Universiti Teknologi MARA Cawangan Pahang, 2019)
Zea mays or commonly known as corn is one of the most important crops in the world. The large production of corn will be associated with the massive use of fertilizer that cost a lot of money. Nowadays, monosodium glutamate (MSG) was known to be used as alternative fertilizer. Despite its widespread use as food flavor, MSG was reported to show a positive effect on plant growth when used as fertilizer. However, the recent studies use MSG industrial wastewater as fertilizer which has an unknown chemical compound and changes the pH of the soil. This study focused on using commercial MSG (Ajinomoto) that is safer as the source of MSG. Hence, this study aims to determine the effects of commercial MSG towards the growth of corn plant. The plants were treated in this study using 1% w/v, 5% w/v and 10% w/v of commercial MSG. The MSG was supplied 3 times per week for 6 weeks. The result suggests that 10% w/v MSG gave the most rapid growth towards Z. mays plant. The plant's height, stem's diameter, number, and length of leaves increased 3.1 folds, 2.6 folds, 2.5 folds, and 2.7 folds respectively compared to control. Hence, this study was the first to report that Ajinomoto MSG has a positive effect on the corn plant and suitable to be used as a low-cost green practice fertilizer